Classification of design parameters for E-commerce websites: A novel fuzzy Kano approach. Issue 8 (December 2017) - Ilbahar, Esra; Cebi, Selcuk
Highlights: The e-commerce websites utilized in Turkey are examined using their design parameters. An integrated approach is proposed for the assessment of e-commerce websites. A novel approach is proposed to classify design parameters. The classification is performed based on customer expectations using Fuzzy Kano Model. Abstract: Websites have gained vital importance for organizations along with the growing competition in the world market. It is known that usability requirements heavily depend on the type, audience and purpose of websites. For the e-commerce environment, usability assessment of a website is required to figure out the impact of website design on customer purchases. Thus, usability assessment and design of online pages have become the subject of many scientific studies. However, in any of these studies, design parameters were not identified in such a detailed way, and they were not classified in line with customer expectations to assess the overall usability of an e-commerce website. This study therefore aims to analyze and classify design parameters according to customer expectations in order to evaluate the usability of e-commerce websites in a more comprehensive manner. Four websites are assessed using the proposed novel approach with respect to the identified design parameters and the usability scores of the websites are examined. It is revealed that the websites with high usability score are more preferred by customers. Therefore, it is indicated that usability of e-commerce websites affects customer purchases.